Simple and efficient synthesis of 3,4-dihydropyrimidin-2(1H)-thiones utilizing l-proline nitrate as a proficient, recyclable and eco-friendly catalyst - Sandeep P. Bahekar; Prashant B. Sarode; Murlidhar P. Wadekar; Hemant S. Chandak (Journal of Saudi Chemical Society, 2017)
A convenient method has been described for eco-friendly synthesis of 3,4-dihydropyrimidin-2(1H)-thiones in the presence of l-proline nitrate as a green amino acid ionic liquid (AAIL) under mild conditions. This greener synthetic method offers benefits like higher yields, shorter reaction times and simple work-up. Easy recyclability of the bio-compatible catalyst makes this protocol attractive, economic and environmentally-benign.